Treatment of bilateral idiopathic trigeminal neuralgia by radiofrequency thermocoagulation at different temperatures. Issue 29 (July 2016) - Yao, Peng; Hong, Tao; Wang, Zhi-bin; Ma, Jia-ming; Zhu, Yong-qiang; Li, Hong-xi; Ding, Yuan-yuan; Jiang, Chang-lin; Pan, Shi-nong
Abstract : Abstract: Radiofrequency thermocoagulation (RFT) is an effective treatment for trigeminal neuralgia, but consensus regarding an optimal treatment temperature is lacking. While treatment temperatures ranging from 60°C to 95°C have been reported, RFT at too high a temperature is often followed by serious complications, and comparative evaluations of RFT at different temperatures in a single study are rare. This current prospective cohort study was to compare immediate and long-term outcomes of RFT at varying temperatures in patients with bilateral idiopathic trigeminal neuralgia (ITN) of maxillary division of trigeminal nerve (V2), mandibular division of trigeminal nerve (V3), and V2+V3, including pain relief, complications, recurrence rate, and patient satisfaction. From May 2011 to April 2016, 62 consecutive patients with bilateral ITN of V2, V3, and V2+V3 were enrolled in the study. These patients underwent bilateral RFT at 68°C and 75°C, respectively, using the same RF parameters. Side-to-side results, including pain relief, complications, and patient satisfaction, were compared during a 5-year follow-up period. Overall pain relief was satisfactory after RFT. The rate of pain relief after treatment at 75°C was slightly higher than at 68°C ( P > 0.05). The pain-free rate was 95.1% at 75°C and 93.5% at 68°C at 1 year, 84.3% and 78.1% at 3 years, and 80.7% and 74.4% at 5 years. There were 10 and 13 cases of recurrence, respectively, and 6 cases of bilateral recurrence. The incidence and severity of complications were greater at 75°C ( P < 0.05) than at 68°C, and therefore the patient satisfaction at the higher temperature was lower ( P < 0.05). Patients with bilateral ITN who underwent RFT at different temperatures had consistent pain relief after RFT at both 75°C and 68°C, but there were fewer and less severe complications at 68°C, which was accompanied by greater patient satisfaction. This suggests that RFT at lower temperatures may be preferable, and that a temperature of 68°C can be recommended.